2021
DOI: 10.14639/0392-100x-n0752
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of migraine vertigo in overlapping syndrome with Ménière’s disease: prognostic role of instrumental examination

Abstract: Introduction. Migraine vertigo (MV) and Ménière's disease (MD) share several signs and symptoms such as tinnitus, fullness, photophobia, phonophobia, headache and vertigo spells lasting hours. Objective. The aim of the present study was to prospectively observe patients with MV with a sporadic audiological symptom evaluated with clinical examination, Vestibular Evoked Myogenic Potentials (VEMPs), ECochG and v-HIT. Results. The finding of VEMP asymmetry, according to our cut-off of 33% of difference between sid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…6% of Mi + experienced time distortion: "everything suddenly slowing down and moving very slowly even if [they were] driving at 80 mph on a highway"; occurred 1 day after Mi and lasted 5 min MA + found these experiences more fascinating than worrisome Celebisoy et al [ 44 ] Vestibular M: n = 415, 42 ± 12 (17–74), 15% 10% of N reported hearing loss in audiometry; 41% of N reported tinnitus; 69% of N reported vertigo attacks lasting 60 min–24 h; 62% of N reported vertigo attacks associated with headache in > 50% of the attacks; median vertigo attack severity = 7 a N/A 42% of N reported photophobia or phonophobia 32% of N reported aural fullness; 20% of N reported osmophobia; 12% of N reported AL Demarquay et al [ 45 ] n = 74 Mi + ( n = 48 non-olfactory hypersensitive (OH-), n = 26 olfactory hypersensitive (OH +)), n = 30 HC; Mi + 42 ± 12; OH- 41 ± 13, OH + 44 ± 10, HC: 38 ± 12; Mi + 18%, OH- 15%, OH + 23%, HC 27% 23% of OH- had non-olfactory established aura; 15% of OH + had non-olfactory established aura N/A N/A 35% of Mi + had interictal olfactory hypersensitivity. OH + judged odours as less pleasant than OH- ( p = 0.002) and controls ( p = 0.006) Dispenza et al [ 19 ] n = 30 Mi + with vertigo; 45 (range 18–64 yrs), 20% n = 12 VA; all had vertigo; n = 10 had episodic tinnitus N/A n = 20 patients reported dizziness and unsteadiness. All had photophobia, n = 26 patients reported phonophobia n = 20 had transitory ear fullness sensation, of which n = 9 had both symptoms after first pure tone audiometry testing Gossrau et al [ 46 ] Mi: n = 113, 46 ± 14, 12% 44% of N reported Mi with aura N/A N/A 38%, 62% and 32% of n = 113 reported preictal, ictal and interictal hypersensitivity to odours respectively; common feared od...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6% of Mi + experienced time distortion: "everything suddenly slowing down and moving very slowly even if [they were] driving at 80 mph on a highway"; occurred 1 day after Mi and lasted 5 min MA + found these experiences more fascinating than worrisome Celebisoy et al [ 44 ] Vestibular M: n = 415, 42 ± 12 (17–74), 15% 10% of N reported hearing loss in audiometry; 41% of N reported tinnitus; 69% of N reported vertigo attacks lasting 60 min–24 h; 62% of N reported vertigo attacks associated with headache in > 50% of the attacks; median vertigo attack severity = 7 a N/A 42% of N reported photophobia or phonophobia 32% of N reported aural fullness; 20% of N reported osmophobia; 12% of N reported AL Demarquay et al [ 45 ] n = 74 Mi + ( n = 48 non-olfactory hypersensitive (OH-), n = 26 olfactory hypersensitive (OH +)), n = 30 HC; Mi + 42 ± 12; OH- 41 ± 13, OH + 44 ± 10, HC: 38 ± 12; Mi + 18%, OH- 15%, OH + 23%, HC 27% 23% of OH- had non-olfactory established aura; 15% of OH + had non-olfactory established aura N/A N/A 35% of Mi + had interictal olfactory hypersensitivity. OH + judged odours as less pleasant than OH- ( p = 0.002) and controls ( p = 0.006) Dispenza et al [ 19 ] n = 30 Mi + with vertigo; 45 (range 18–64 yrs), 20% n = 12 VA; all had vertigo; n = 10 had episodic tinnitus N/A n = 20 patients reported dizziness and unsteadiness. All had photophobia, n = 26 patients reported phonophobia n = 20 had transitory ear fullness sensation, of which n = 9 had both symptoms after first pure tone audiometry testing Gossrau et al [ 46 ] Mi: n = 113, 46 ± 14, 12% 44% of N reported Mi with aura N/A N/A 38%, 62% and 32% of n = 113 reported preictal, ictal and interictal hypersensitivity to odours respectively; common feared od...…”
Section: Resultsmentioning
confidence: 99%
“…The most common postdromal and prodromal symptoms were photophobia ( n = 19) and phonophobia ( n = 16). A large proportion of people with migraine with aura experienced headaches after the onset of the aura, of which most individuals experienced headache during the aura, or within 30 min after the cessation of the aura [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…In case of ELH, the ECochG shows a typical pattern characterized by an alteration of the ratio between summation potential and action potential (SP/AP): an SP/AP amplitude ratio higher than 0.35 and an SP/AP area ratio higher than 1.94 are considered as indicators of ELH (11,14,21). Therefore, despite ECochG is limited because of its low sensitivity and its reliability is strictly dependent on the type of electrode used, type of stimulus given, and stage of MD, it could be still considered a useful tool both in the diagnosis and in the monitoring of instrumental features and clinical symptoms related to ELH.…”
Section: Discussionmentioning
confidence: 99%
“…ELH was present per this test in 70.6% of patients with MD and 50% of VM patients [36 && ]. The presence of ELH has been thought to be indicated by electrocochleography (EcochG) and calculation of cochlear summating potential and auditory nerve action potential (SP/AP) ratio >0.5 [38,39]. Recent studies have shown 12 of 30 VM cases with episodic audiologic dysfunction positive for ELH, 3 of 21 cases of VM with no audiologic component positive for ELH, and 8 of 21 VM patients with unspecified cochlear symptoms [38][39][40].…”
Section: Endolymphatic Hydropsmentioning
confidence: 99%